Drop Impact Behavior on Food Using Spray Coating: Fundamentals and Applications - Osorio-Lira, F; Andrade-Pizarro, R (2013)
Spray coating is among the most commonly used methods to coat foods, especially fruits. To obtain high quality of coated products the properties of the material to be coated, the properties of coating-forming solutions, method of coating, temperature and contact time between food and coating material should be optimized. In spray coating, drops are impacted and may rebound, splash, or deposit cleanly as is desirable. This review discusses the importance of the drop impact behavior on food using spray coating. The main parameters affecting the behavior such as: physico-chemical characteristics of the liquid, velocity of impact, and physical properties of the food are discussed. Models applied to predict different parameters of drop behavior after impact are presented. © 2013 Elsevier Ltd.